Structure of the Fundamental Solution of Cauchy Problem for Kolmogorov Systems of Second-Order - Burtnyak, I.; Malytska, H. (Journal of Vasyl Stefanyk Precarpathian National University, 2015)
We study a structure of the fundamental solution of the Cauchy problem for a class of ultra parabolic equations with a finite number of groups of variables with degenerated parabolicity.